Desperate Measures: Stone Barrington #47 - Woods, Stuart (New York : G.P. Putnam's Sons, 2018)
"Stone Barrington is ready for anything--and up against a problem that could cost him everything--in the newest thriller from perennial fan favorite and #1 New York Times--bestselling author Stuart Woods" --.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Mystery fiction; Suspense fiction